Efficacy of Systemic Biologic Drugs in Pediatric Psoriasis: Evidence From Five Selected Randomized Clinical Trials - Di Lernia, Vito; Macca, Laura; Peterle, Lucia; Ingrasciotta, Ylenia; Trifirò, Gianluca; Guarneri, Claudio (Frontiers in Pharmacology, 2022)
Background: Psoriasis is a chronic, immune-mediated skin disease that may occur at any age. Prevalence in children ranges between 0.5%−1.0% across Europe. Approximately 10−20% of paediatric psoriasis patients are moderate-to-severe in severity and may require the use of systemic therapy. Objective: Recently, newer targeted, systemic therapies have been licensed for treatment of moderate-to-severe pediatric psoriasis. The objective of this study was to evaluate the short-term efficacy of available antipsoriatic systemic drugs in in children with a narrative synthesis of key efficacy from randomized clinical trials. Methods: A systematic review of literature was performed on Medline and Embase databases and the Cochrane Central Register of Controlled Trials. Randomized clinical trials investigating the efficacy of treatments licensed by the US Food and Drug Administration and/or the European Medicines Agency for pediatric and adolescent psoriatic population were retrieved and analyzed. Data from this literature review was assessed in line with GRADE (grading of recommendations, assessment, development and evaluations). The short-term (12-16 weeks) clinical efficacy from baseline was evaluated according to the Psoriasis Area and Severity Index (PASI) 75 and 90 compared to baseline. Absolute and relative risk (RR) and the number needed to treat (NNT) for response on PASI 75 and PASI 90 were extracted. Results: A total of five relevant studies were identified on two TNF-alpha blockers (etanercept and adalimumab), an anti-IL12/23 inhibitor (ustekinumab), two anti- IL-17 inhibitors (ixekizumab, secukinumab). Comparators were placebo (3 studies), placebo and etanercept (1 study) methotrexate (1 study). All examined drugs resulted efficacious. The probability to achieve PASI 75 and PASI 90 was higher for the anti-IL12/23 and anti-IL17 inhibitors. Overall, anti-IL17 inhibitors and the anti-IL12/23 showed a more favorable NNT for PASI 75, anti-IL17 inhibitors for PASI 90. Conclusions: the approved biological therapies may be beneficial for the treatment of moderate to severe plaque psoriasis in children and adolescents. Since psoriasis is a chronic and often challenging condition with no definitive solution, systematic evaluations of long-term efficacy, drug survival and adverse effects may help careful, individualized, patient-centered clinical decision making.